За і проти чинника некрозу пухлин альфа як маркера ожиріння та інсулінорезистентності на прикладі клінічного дослідження - Кіхтяк, О. П. (Clinical Endocrinology and Endocrine Surgery, 2009)
Four month treatment with either pioglitazone or metformin in diabetics with obesity showed statistically relevant improvement of the certain list of markers: fasting glucose, HOMA-IR index, HbA1c, and tumour necrosis factor alpha (TNF-α). Taking all patients into account we did not confirm an inverse correlation between TNF-α and body mass index (BMI) or waist circumference, but association between TNF-α and HOMA-IR index was established. We speculate that TNF-α may be recognised as additional marker of insulin resistance but not with changes in BMI in type 2 diabetic patients.